2005
DOI: 10.1123/japa.13.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Factors Influencing Older Adults Diagnosed with Knee Osteoarthritis to Join and Maintain an Exercise Program

Abstract: In order to provide successful interventions to increase physical activity among inactive older adults, it is imperative to understand motivational factors influencing exercise. The authors present data from 191 (baseline) and 125 (12-month) community-dwelling men and women with mean ages of 68.71 (7.47) and 67.55 (7.55) years, respectively, from a strength-training trial. Approximately 53% had diagnosed knee osteoarthritis. Using a Likert scale, participants self-reported their degree of motivation from perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
70
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 29 publications
7
70
0
1
Order By: Relevance
“…14,15 However, people with OA seem to exercise less frequently than the general population, 16 and exercise adherence is a common problem among these people. [17][18][19] Factors that may play an important role in explaining the exercise behavior of people with OA include self-confidence and self-efficacy, 14,17,19 -21 knowledge of the disease and the effects of exercise, 14,18,20 -22 the support and attitude of others, 14,18,20 -24 mental health, 21 and former experience of exercising. 14,18,20,22 Pain and stiffness are common symptoms of arthritis that also can have a significant impact on the attitude and capability of people to exercise, 22,25 as well as the common misunderstanding that OA is something that comes naturally with older age and that nothing can be done about it.…”
Section: Conclusion Increased Knowledge and Understanding Of The Famentioning
confidence: 99%
“…14,15 However, people with OA seem to exercise less frequently than the general population, 16 and exercise adherence is a common problem among these people. [17][18][19] Factors that may play an important role in explaining the exercise behavior of people with OA include self-confidence and self-efficacy, 14,17,19 -21 knowledge of the disease and the effects of exercise, 14,18,20 -22 the support and attitude of others, 14,18,20 -24 mental health, 21 and former experience of exercising. 14,18,20,22 Pain and stiffness are common symptoms of arthritis that also can have a significant impact on the attitude and capability of people to exercise, 22,25 as well as the common misunderstanding that OA is something that comes naturally with older age and that nothing can be done about it.…”
Section: Conclusion Increased Knowledge and Understanding Of The Famentioning
confidence: 99%
“…While numerous strategies are suggested to help improve adherence to exercise interventions in people with OA (9,13,28), there are few RCTs in this area. A 2010 Cochrane Review of adherence strategies in chronic musculoskeletal pain, including OA, stated that the most promising strategies are those that include supervised exercise, individualized exercise, booster sessions, provision of supplementary materials such as exercise audiotapes/ videotapes, and that incorporate graded activity, selfmanagement programs, and cognitive behavioral principles (13).…”
mentioning
confidence: 99%
“…Studies have identified both internal and external facilitators and barriers to exercise (28,29,31). Internal factors include individual attributes such as motivation, personality, self-image, exercise attitude, exercise history, and disease knowledge, as well as personal experience.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…56,57 In a study of 191 older adults with knee pain and osteoarthritis, the desire to improve their health and the expectation that exercise would accomplish this were the most significant motivators for participation in an exercise program. 58 Similarly, self-efficacy, or belief in the ability to perform a required behavior to produce an outcome, was a significant predictor of postoperative exercise in 50 patients who had had total knee or total hip replacements. 59 Imagining a desired future and the processes to attain it is hypothesized to increase motivation and effort.…”
Section: Psychological Variables and Tkr Outcomesmentioning
confidence: 99%